Advances in cell membrane-based biomimetic nanodelivery systems for natural products - Yifeng Zhang; Qian Zhang; Chunhong Li; Ziyun Zhou; Hui Lei; Minghua Liu; Dan Zhang (Taylor & Francis Group, 2024)
Active components of natural products, which include paclitaxel, curcumin, gambogic acid, resveratrol, triptolide and celastrol, have promising anti-inflammatory, antitumor, anti-oxidant, and other pharmacological activities. However, their clinical application is limited due to low solubility, instability, low bioavailability, rapid metabolism, short half-life, and strong off-target toxicity. To overcome these drawbacks, cell membrane-based biomimetic nanosystems have emerged that avoid clearance by the immune system, enhance targeting, and prolong drug circulation, while also improving drug solubility and bioavailability, enhancing drug efficacy, and reducing side effects. This review summarizes recent advances in the preparation and coating of cell membrane-coated biomimetic nanosystems and in their applications to disease for targeted natural products delivery. Current challenges, limitations, and prospects in this field are also discussed, providing a research basis for the development of multifunctional biomimetic nanosystems for natural products.